Penyuluhan Pengembangan Peternakan Itik di Kota Sawahlunto - Robi Amizar; Wizna Wizna; Mirzah Mirzah; Rusfidra Rusfidra; Yuherman Yuherman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Sawahlunto city is one of the cities/districts in West Sumatra actively assisting the poor. The assistance was given was livestock for farmers, such as goats, ducks, and native chickens. In 2020 the population of ducks in Sawahlunto was recorded at 18,654 ducks with 257 farmers. In 2022, there is a giving of 100 ducks to a breeder by the related government. The ducks are farmed in four sub-districts, i.e. Talawi, Barangin, Lembah Segar, and Silungkang Districts. The society target of the activity was duck breeders under the Food Security, Agriculture, and Fisheries Service of Sawahlunto City. The main problem of them is high feed prices and difficulty developing breeders. The knowledge transfer from academics to farmers was carried out by counselling and discussions about good production, nutrition, and livestock health. This activity was carried out during the Covid-19 pandemic, which was still restricted by social distancing protocol. The discussion was attended by around 137 participants consisting of 70 poultry farmers, 30 agricultural assisting workers, and 37 local heads in Sawahlunto City.